Pengaruh Waktu Penyimpanan Ekstrak Buah Naga (Hylocereus polyrhizus) sebagai Pewarnaan Alternatif Eosin Pada Sediaan Hepar Mencit (Mus musculus) - Ramadhani, Falah Aiken; Rahmawati, Yeni; Shafriani, Nazula Rahma (Universitas Mohammad Husni Thamrin, 2025)
Histotechnics aims to identify tissue structure through a staining process, one of which uses eosin which has dangerous side effects and is expensive. The purpose of this study was to test the stability of dragon fruit extract (Hylocereus polyrhizus) as a substitute for eosin staining in mouse liver tissue (Mus musculus) with varying storage times of 10 days and 15 days. This research method used a quasi-experimental with a descriptive approach. Staining was carried out on 12 preparations divided into three groups: control (eosin), 10-day extract, and 15-day extract. The results showed that the best staining was obtained in the control group for total scoring 60, while the 10-day extract group produced a fairly good total scoring staining quality 31, and the 15-day group showed a decrease in total scoring staining quality 23. The results of this study revealed that dragon fruit extract has the potential as an alternative eosin staining, especially after 10 days of storage, but its effectiveness decreased after 15 days of storage. Further research recommendations include optimizing extract stability to extend the shelf life of natural dyes. Keywords: Dragon Fruit (Hylocereus polyrhizus), Eosin, Histology..